Feline Exocrine Pancreatic Insufficiency: A Retrospective Study of 150 Cases. (19th September 2016) - Xenoulis, P.G.; Zoran, D.L.; Fosgate, G.T.; Suchodolski, J.S.; Steiner, J.M.
Abstract : Background: Little information is available about the clinical presentation and response to treatment of cats with exocrine pancreatic insufficiency (EPI). Objectives: To describe the signalment, clinical signs, concurrent diseases, and response to treatment of cats with EPI. Animals: One hundred and fifty cats with EPI. Methods: Retrospective case series. Results: Questionnaires were sent to 261 veterinarians, and 150 (57%) were returned with data suitable for statistical analysis. The median age of the cats with EPI was 7.7 years. The median body condition score was 3 of 9. Ninety‐two of 119 cats (77%) had hypocobalaminemia, and 56 of 119 cats (47%) had increased and 6 of 119 cats (5%) had decreased serum folate concentrations. Clinical signs included weight loss (91%), unformed feces (62%), poor hair coat (50%), anorexia (45%), increased appetite (42%), lethargy (40%), watery diarrhea (28%), and vomiting (19%). Eighty‐seven cats (58%) had concurrent diseases. Treatment response was reported to be good in 60%, partial in 27%, and poor in 13% of 121 cats. Trypsin‐like immunoreactivity <4 μg/L was associated with a positive response to treatment (OR, 3.2; 95% CI, 1.5–7.0; P = .004). Also, cobalamin supplementation improved the response to treatment (OR, 3.0; 95% CI, 1.4–6.6; P = .006). Conclusions and Clinical Importance: Exocrine pancreatic insufficiency in cats often has a different clinical presentation than in dogs. The age range for EPI in cats is wide, and many cats can be ≤5 years of age. Most cats respond well to appropriate treatment for EPI, and cobalamin supplementation appears to be necessary for a good response.